The dual purpose of high spatiotemporal resolution of electronic monitoring data in fisheries: sustain fisheries and enhance protection of sensitive habitats - Nielsen, Pernille; Olsen, Jeppe; Geitner, Kerstin; Petersen, Jens Kjerulf (Frontiers in Marine Science, 2025)
Fisheries using bottom-towed fishing gears are a localised pressure that causes physical disturbance to the seabed habitats. To meet the requirements of ecosystem-based fisheries management, it is essential to have high-resolution remote electronic monitoring fisheries data with appropriate spatial resolution to evaluate the direct impact of fishing activities. The resolution of the fishery data must align with both the spatial operational characteristics of the fishery and the conservation objectives under review, such as habitat and species distribution. Here we show how Black Box (BB) data logging actual fishing activity locations can be used to assess the direct footprint of bivalve fishing on eelgrass meadows. Our findings demonstrated that i) Actual logged fishing tracks (BB data) can document no overlap with known observations of eelgrass meadows, while low-resolution fisheries data (VMS data) showed an overlap with eelgrass meadows. Furthermore, the VMS data from a few vessels showed 2.5 greater overlap with areas assessed as suitable for eelgrass compared to actual tracks logged by the BB from the entire fleet. These findings emphasise the importance of equipping fishing vessels with electronic monitoring systems that capture actual fishing activity locations. This enables us to accurately track the areas impacted by fisheries, and when combined with high-resolution habitat monitoring, it facilitates ecosystem-based fishery management and ensures the achievement of nature conservation goals.